Synthesis of high molecular weight polybenzimidazole using a highly pure monomer under mild conditions - Kim, Eun-Ki; Lee, So Young; Nam, Sang Yong; Yoo, Sung Jong; Kim, Jin Young; Jang, Jong Hyun; Henkensmeier, Dirk; Kim, Hyoung-Juhn; Lee, Jong-Chan (WILEY, 2017)
An isophthalaldehyde bisulfite adduct (IBA) was synthesized using a reaction between sodium sulfite and isophthalaldehyde. Isophthalaldehyde monosulfite adduct (IMA) was inevitably synthesized during the reaction. Because IBA and IMA have similar solubility in water, it is difficult to separate them through a recrystallization process. In order to obtain pure IBA, an excess of sodium sulfite was used. Highly pure IBA was subsequently obtained without the need for recrystallization. The IBA was then used as the starting monomer for the synthesis of poly[2,2-(m-phenylene)-5,5-bisbenzimidazole] (PBI). Previous isolation methods for IBA hindered the synthesis of high molecular weight PBI. This new synthetic procedure produces high-purity IBA, which can be used to synthesize high molecular weight PBI. (c) 2017 Society of Chemical Industry